2018
DOI: 10.1088/1612-202x/aaef95
|View full text |Cite
|
Sign up to set email alerts
|

Shaping triangular picosecond laser pulses for electron photoinjectors

Abstract: Beam driven wakefield acceleration is one of the most advanced novel accelerator concepts. This process occurs in a plasma or a slow-wave structure in which the drive beam deposits energy in the form of a wake and the main beam is accelerated by this wake. For efficient acceleration, it is important to shape the drive beam current and to increase the so-called transformer ratio: the energy gain by the main beam to the energy loss of the drive beam. Triangular bunch shapes are among the most promising distribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Before amplification, the pulses are profiled to provide the necessary (close to rectangular) shape of the pump pulse of the intermediate, booster and final parametric amplifiers. Since the pulses are chirped, it is convenient to use the spectral approach for their profiling [ 42 , 43 ] . This approach allows tuning the delay in few ps range with approximately kHz resolution to suppress a temporal jitter on ps parametric stages.…”
Section: Exawatt Center For Extreme Light Studies Lasermentioning
confidence: 99%
See 1 more Smart Citation
“…Before amplification, the pulses are profiled to provide the necessary (close to rectangular) shape of the pump pulse of the intermediate, booster and final parametric amplifiers. Since the pulses are chirped, it is convenient to use the spectral approach for their profiling [ 42 , 43 ] . This approach allows tuning the delay in few ps range with approximately kHz resolution to suppress a temporal jitter on ps parametric stages.…”
Section: Exawatt Center For Extreme Light Studies Lasermentioning
confidence: 99%
“…This requires a pump pulse energy of at least 100 J with a quasi-rectangular pulse duration of 3.5 ns, which ensures overlap between the pump pulse and the 3-ns chirped pulse. The quasi-rectangular shape of the pulse is provided by profiling the output pulse [ 42 , 43 ] in the frontend (point 1.2 in Figures 1 and 3). Secondly, the intermediate OPCPA ensures the operation of the XCELS laser with a multipetawatt power and a repetition rate significantly higher than two pulses per day (point 2.2 in Figure 1).…”
Section: Exawatt Center For Extreme Light Studies Lasermentioning
confidence: 99%
“…The first beam physics applications used an SLM system to convert a Gaussian pulse of 9 ps FWHM to a flattop pulse of the same length to drive a photocathode RF gun (Yang et al, 2002). Gaussian pulses were transformed into both triangular and super-triangular laser pulses with an SLM-based system (Kuzmin et al, 2018) as shown in Fig. 14.…”
Section: A Frequency Domain Laser Shapingmentioning
confidence: 99%
“…A downstream dispersive section with longitudinal dispersion ξ + and designed to suppress the dispersion introduced by the section upstream of the mask results in the overall shaping function f [x m /(ηh 0 )]. This technique bears similarities with the frequency-domain temporal shaping method commonly encountered in ultrafast laser shaping, where a frequency-chirped laser is dispersed, its spectrum modified with a mask, and subsequently recombined (Kuzmin et al, 2018;Weiner et al, 1988); see Section III.D.3.a.…”
Section: Local Coupling Combined With Transverse Maskingmentioning
confidence: 99%
See 1 more Smart Citation